Impacts of Irritable Bowel Syndrome associated with anxiety and depression on the quality of life of the population (Research, Society and Development, 2023)
Irritable Bowel Syndrome (IBS) is a functional gastrointestinal disorder (GIF) that affects the individual chronically. In addition, it is a pathology associated, in the vast majority of cases, with psychological factors, such as anxiety and depression. The objective of this study is to verify the impacts of IBS combined with mental disorders on the quality of life of the general population and also to identify the benefits of different types of treatments in the symptomatology of the disease. Considering this, this article is a systematic review of the literature, with the purpose of answering the following question: “What are the impacts that irritable bowel syndrome associated with anxiety and depression can bring to the quality of life of the general population?”. Among the criteria was the date of publication, between 2012 and 2022, found in databases such as the Virtual Health Library (BVS), Scientif Electronic Library Online (SciELO), National Library of Medicine (PubMed), EbscoHost. Thirty articles were identified, of which 23 fit the pre-established criteria. It can be seen that, undeniably, psychological disorders such as anxiety and depression are shown to cause this clinic, therefore psychological and pharmacological accompaniments as a treatment, associated with a healthy diet, are very effective in improving the quality of life of these patients.